Protection against ß-amyloid-induced synaptic and memory impairments via altering ß-amyloid assembly by bis(heptyl)-cognitin - ROWAN, MICHAEL; ANWYL, ROGER; ROWAN, MICHAEL JOSEPH; ANWYL, ROGER (My University, 2015)
β-amyloid (Aβ) oligomers have been closely implicated in the pathogenesis of Alzheimer’s disease (AD). We found, for the first time, that bis(heptyl)-cognitin, a novel dimeric acetylcholinesterase (AChE) inhibitor derived from tacrine, prevented Aβ oligomers-induced inhibition of long-term potentiation (LTP) at concentrations that did not interfere with normal LTP. Bis(heptyl)-cognitin also prevented Aβ oligomers-induced synaptotoxicity in primary hippocampal neurons. In contrast, tacrine and donepezil, typical AChE inhibitors, could not prevent synaptic impairments in these models, indicating that the modification of Aβ oligomers toxicity by bis(heptyl)-cognitin might be attributed to a mechanism other than AChE inhibition. Studies by using dot blotting, immunoblotting, circular dichroism spectroscopy, and transmission electron microscopy have shown that bis(heptyl)-cognitin altered Aβ assembly via directly inhibiting Aβ oligomers formation and reducing the amount of preformed Aβ oligomers. Molecular docking analysis further suggested that bis(heptyl)-cognitin presumably interacted with the hydrophobic pockets of Aβ, which confers stabilizing powers and assembly alteration effects on Aβ. Most importantly, bis(heptyl)-cognitin significantly reduced cognitive impairments induced by intra-hippocampal infusion of Aβ oligomers in mice. These results clearly demonstrated how dimeric agents prevent Aβ oligomers-induced synaptic and memory impairments, and offered a strong support for the beneficial therapeutic effects of bis(heptyl)-cognitin in the treatment of AD.
PUBLISHED
Keywords: β-amyloid (Aβ); β-amyloid (Aβ)